2011
DOI: 10.1007/s11661-011-0678-z
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Retained Austenite in High-Al, Low-Si TRIP-Assisted Steels Processed via Continuous Galvanizing Heat Treatments

Abstract: Two galvanizable high-Al, low-Si transformation-induced plasticity (TRIP)-assisted steels were subjected to isothermal bainitic transformation (IBT) temperatures compatible with the continuous galvanizing (CGL) process and the kinetics of the retained austenite (RA) to martensite transformation during room temperature deformation studied as a function of heat treatment parameters. It was determined that there was a direct relationship between the rate of straininduced transformation and optimal mechanical prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 35 publications
0
26
0
Order By: Relevance
“…Recently, McDermid et al [36] showed that while the strain-based model (Eq. 4, [12]) could successfully describe the kinetics of the RA to martensite transformation, a simple normalised plastic flow stress model (Eq.…”
Section: Factors Affecting the Retained Austenite Stabilitymentioning
confidence: 99%
“…Recently, McDermid et al [36] showed that while the strain-based model (Eq. 4, [12]) could successfully describe the kinetics of the RA to martensite transformation, a simple normalised plastic flow stress model (Eq.…”
Section: Factors Affecting the Retained Austenite Stabilitymentioning
confidence: 99%
“…Two different forms of retained austenite are described in the literature. On the one hand, film‐like retained austenite between the martensite lathes (interlathe film), respectively, between the bainitic lathes, and, on the other, grains of retained austenite . After the employed heat treatments, retained austenite mainly exists as polygonal shaped grains.…”
Section: Discussionmentioning
confidence: 99%
“…Like in the work of Santofimia et al, the grains of retained austenite were particularly observed between primary martensite and ferrite or secondary martensite and ferrite. In TRIP steels, retained austenite occurs in a similar way, isolated or granular surrounded by ferrite or bainite or at their grain boundaries . A film‐like formation between the bainite lathes is also known.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations